THE ROLE OF THE INTERNATIONAL MONETARY FUND IN PROMOTING GLOBAL ECONOMIC STABILITY - Alina HAGIU; Luiza Madalina APOSTOL (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2017)
This paper presents the role that the International Monetary Fund performs in promoting global economic stability. Global economic and financial stability plays a key role in the financial system and the economy as a whole. The increase in the importance of the concept of financial stability by supervisors at both European and global level was concretized by defining a framework for the operationalization of macroprudential policy, together with the establishment of coordination bodies in this field, thus recognizing its role in the mix of established economic policies such as monetary, fiscal or competitive policy.